The Effect of Psychosocial Stressors on the Degree of Vasomotor Complaints in Menopausal Women - I Wayan Agung Indrawan; Suheni Ninik; Edy Mustofa; Rahajeng Rahajeng; Numbi Herizasiwi (Journal of Issues in Midwifery, 2022)
BACKGROUND: Menopause is a condition when the menstrual cycle stops which causes the development of ovarian follicles. Vasomotor symptoms are the main complaints of menopause and often include hot flashes and night sweats. In Indonesia, the relationship between psycho-social stressors on vasomotor symptoms during menopause is still not well implemented.OBJECTIVE: The purpose of this study was to determine the effect of psychosocial stressors on vasomotor symptoms in menopausal women.METHOD: This study is an analytical study using a cross-sectional study design. patient. The interview and filling out the Holmes and Rahe questionnaire were conducted in a private counseling room at the outpatient RSSA. This research uses structural model analysis with Partial Least Square approach to test the proposed hypothesis. Each hypothesis will be analyzed using SmartPLS 3.0 software to test the relationship between variables.RESULTS: Vasomotor symptoms are mostly complained by perimenopause women, high psychosocial stressors having a significant effect on the severity of the vasomotor symptoms (p = 0.039).CONCLUSION: Psychosocial stressors have a significant direct effect on the degree of vasomotor symptoms. Further studies are needed with a more adequate sample size, more diverse variables and a longer follow-up time to ascertain the factors that have a significant relationship with the degree of vasomotor symptoms.